Words of wisdom from mother runners: Using creative non-fiction advice letters to show psycho-social tensions and strategies influencing performance - Kerry R. McGannon; Jenny McMahon (Asian Journal of Sport and Exercise Psychology)
Although motherhood is a well-documented time when recreational sport pursuits decline, researchers have shown that some women participate in sport after becoming mothers. Recreational running is one sport where mothers (re)negotiate their subjectivity in ways that resist constraining good mother ideals by expanding strategies to enhance well-being. There remain nuanced tensions in this process that are less understood, particularly in terms of how mother runners negotiate training and competing. In this study, we used relativist narrative inquiry to explore these tensions and performance strategies of five North American competitive mother runners with young children, theorized as stories in cultural narratives. We used thematic narrative analysis to identify a theme of patience with the process: it's a long and winding road. We then shifted to storytellers to present the meanings of this theme as three accessible creative non-fiction (CNF) letters of advice to other potential mother runners. Advice letters outlined strategies pertaining to the physical self, a flexible mindset and social support. We reflect on the central theme in relation to narratives of good motherhood, sport performance, and discovery, and the implications for psycho-social tensions and performance strategies. CNF advice letters show the pedagogical potential of different kinds of stories to learn more about the constraining and empowering aspects of sport in mothers’ lives, in cultural context.